Interactions Between Bacillus Spp., Pseudomonas Spp. and Cannabis sativa Promote Plant Growth - Comeau, Dominique; Balthazar, Carole; Novinscak, Amy; Bouhamdani, Nadia; Joly, David L.; Filion, Martin (Frontiers in Microbiology, 2021)
Plant growth promoting rhizobacteria (PGPR) deploy several mechanisms to improve plant health, growth, and yield. The aim of this study was to evaluate the efficacy of two Pseudomonas spp. strains and three Bacillus spp. strains used as single treatments and in consortia to improve the yield of Cannabis sativa and characterize the impact of these treatments on the diversity, structure, and functions of the rhizosphere microbiome. Herein, we demonstrate a significant C. sativa yield increase up to 70% when inoculated with three different Pseudomonas spp./Bacillus spp. consortia but not with single inoculation treatments. This growth promoting effect was observed in two different commercial soil substrates commonly used to grow cannabis: Promix and Canna coco. Marker-based genomic analysis highlighted Bacillus spp. as the main modulator of the rhizosphere microbiome diversity and Pseudomonas spp. as being strongly associated to plant growth promotion. We describe an increase abundance of predicted PGPR metabolic pathways linked with growth promoting interactions in C. sativa.